(untitled) - Callahan, C. A. (Indianapolis, Ind., 2008)
Windows SharePoint Services (WSS) 3.0 is the latest version of the collaboration tool found in Windows Server 2003 R2 and also the underlying technology of Microsoft Office SharePoint Server (MOSS) 2007. In this comprehensive book you’ll go under the hood of WSS 3.0 and discover how to make it easy to share documents, track tasks, create common workspaces where teams can work collectively, set up discussion groups, and more. Includes essential techniques for site creation, administration, customization, security, and disaster recovery, and practical steps for migrating from 2.0 to 3.0.
Keywords: Intranets (Computer networks),Web servers